2018
DOI: 10.3390/ijms19123848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxytocin on Fear Memory and Neuroinflammation in a Rodent Model of Posttraumatic Stress Disorder

Abstract: Posttraumatic stress disorder (PTSD) is a trauma-induced mental disorder characterized by fear extinction abnormalities, which involve biological dysfunctions among fear circuit areas in the brain. Oxytocin (OXT) is a neuropeptide that regulates sexual reproduction and social interaction and has recently earned specific attention due to its role in adjusting neurobiological and behavioral correlates of PTSD; however, the mechanism by which this is achieved remains unclear. The present study aimed to examine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 63 publications
9
24
0
Order By: Relevance
“…We confirmed that ligature-induced periodontal inflammation significantly increased the IL-1β expression levels in the hippocampus through serum IL-6. The mRNA expression level upregulated by ligature is a 1.5-fold change compared with the control, consistent with previous data showing that posttraumatic stress disorder increased IL-1β expression approximately 1.5-fold, which is connected with neurodegenerative disorder [ 45 ]. Sustained increased levels from periodontal inflammation may cause neurodegenerative diseases such as AD.…”
Section: Discussionsupporting
confidence: 90%
“…We confirmed that ligature-induced periodontal inflammation significantly increased the IL-1β expression levels in the hippocampus through serum IL-6. The mRNA expression level upregulated by ligature is a 1.5-fold change compared with the control, consistent with previous data showing that posttraumatic stress disorder increased IL-1β expression approximately 1.5-fold, which is connected with neurodegenerative disorder [ 45 ]. Sustained increased levels from periodontal inflammation may cause neurodegenerative diseases such as AD.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous observation [ 7 , 21 24 ], the acute traumatic stress did not affect fear conditioning or extinction learning, leading to comparable freezing responses between stressed and unstressed mice (Fig. 1 b and e).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with previous reports [7,[22][23][24][25], the acute traumatic stress did not affect fear conditioning or extinction learning, leading to comparable freezing responses between stressed and unstressed mice ( Fig. 1B and E).…”
Section: Behavioral Consequences Of Exposure To Traumatic Stressorssupporting
confidence: 92%